A Study on Experiential Marketing of an Underground Tourist Attraction in Bangkok - Nan , Wi Lai; Batra, A Darsh (Journal of China-ASEAN Studies, 2022)
Maintaining consumer loyalty/revisit to a company, which leads to revisit or repurchase purpose, is a critical element in today’s highly competitive market climate. To ensure longterm market growth in every industry, businesses must first consider their consumers’ desires and then build unique brands. As consequence, if the tourism sector of the country is developing very well, it can help and implement other sectors of the country at the same time. The primary purpose of this research is to study the Experiential Marketing of an underground tourist attraction in Bangkok, Thailand. The objectives of this study are to analyze the influence of experiential marketing on emotion, to identify the influence of experiential quality on experiential satisfaction, to examine the influence of emotion on experiential satisfaction, and to investigate the influence of experiential satisfaction on revisit intention. The data collected at a specified time from February 23, 2021, to March 10, 2021. The questionnaires were hand distributed on weekdays and weekends from 12.00 pm to 6.00 pm at around Siam Square One, Siam Centre, and Siam Paragon in Bangkok by using five-point Likert scale survey questionnaires. The questionnaires were distributed until the sample size was achieved. After the data collecting process, the researchers analyzed all primary data by utilizing the Statistical program. The descriptive analysis and inferential analysis including linear regression analysis were used to test all the hypotheses. According to the study’s findings, experiential marketing (Feel, Sense, Think, Act, Relate) influence is statistically relevant to emotion. Then, experiential quality and emotion also influence experiential satisfaction. Moreover, experiential satisfaction positively influences revisit intention. This study has both time and place limitations which can be difficult to obtain relevant information and difficult to compile data. The value of this study is to promote marketing strategies and to pursue the visitors of Sea Life Bangkok Ocean World.